The Effect of Salicylic Acid Concentration on Callus Induction and Morphology in Young Stem Explants of Momordica cochinchinensis (Lour.) Spreng under In Vitro Conditions - Indayani Tandililing; Jusna Ahmad; Devi Bunga Pagalla; Novri Youla Kandowangko; Indiriati Husain (Agroteknika, 2026)
Dumbaya (Momordica cochinchinensis (Lour.) Spreng.) is a tropical plant with potential as a functional food and natural antioxidant source due to its high bioactive compound content. However, its propagation is constrained by low seed germination caused by a hard seed coat, necessitating alternative methods such as plant tissue culture. This study aimed to evaluate the effect of salicylic acid (SA) concentration on callus induction and morphology in young stem explants of Dumbaya under in vitro conditions. A completely randomized design with five treatments was used: MS medium without plant growth regulators (ID0), MS + 2 mg L⁻¹ 2,4-D + 2 mg L⁻¹ BAP (ID1), and MS supplemented with 88.44 mg L⁻¹ (ID2), 162.14 mg L⁻¹ (ID3), and 235.84 mg L⁻¹ (ID4) SA, each with three replicates. Observed parameters included callus formation percentage, initiation time, color, and texture. All treatments resulted in 100% callus formation at 14 days after inoculation. Analysis of variance indicated a highly significant effect on callus initiation time (F = 156.339; p < 0.001), with the fastest initiation observed in ID2 (3.33 ± 0.00 days) and the slowest in ID0 (8.67 ± 0.33 days). Callus morphology varied in color and was predominantly friable. The ID2 treatment produced the most desirable characteristics, including bright color and friable texture. These findings indicate that 88.44 mg L⁻¹ SA was the most effective concentration for early callus induction and favorable callus morphology in Dumbaya.